Tu było żyć trudno, ale się opłacało… Wielokulturowe skupiska osadnicze na Urzeczu jako przykład długotrwałej i uporządkowanej kolonizacji terenów zalewowych Wisły - Stanaszek, Łukasz Maurycy (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
The article addresses the issue of multicultural settlements from ancient until modern times, located on the Vistula floodplains within Urzecze micro-region. Archaeological, historical and partly ethnographic research indicate an “island” rather than dispersed nature of the local settlement. The separation of clusters allowed to discover many hitherto lost medieval villages or parts of them. The main advantage of long-term settlement on the floodplain was the proximity to a large navigable river (trade, fishing) and fertile soil, compensating for the losses resulting from the frequent floods.